Positive plate and lithium ion secondary battery

By using double-layer coating technology in the positive electrode sheet of lithium ion secondary battery, the grain structure and average particle size of lithium iron phosphate are controlled, and the problems of low energy density and poor circulation performance of lithium ion secondary battery are solved, thereby achieving higher energy density and better circulation stability.

CN119852326AActive Publication Date: 2025-04-18ZHUHAI COSMX POWER BATTERY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411982067.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-18
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The positive electrode sheets of existing lithium-ion secondary batteries have problems of low energy density and poor circulation performance.

Method used

By adopting the double-layer coating technology, the concentration polarization in lithium iron phosphate diffusion is improved by controlling the grain structure and average particle size and distribution of lithium ion diffusion in the first positive electrode coating and the second positive electrode coating. The first positive electrode coating is close to the positive electrode current collector, the second positive electrode coating is away from the positive electrode current collector, and includes first lithium iron phosphate and second lithium iron phosphate with different average particle sizes, respectively.

Benefits of technology

The energy density, cycle stability and service life of lithium-ion secondary batteries are improved, ensuring the stability of battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852326A_ABST
    Figure CN119852326A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a positive plate and a lithium ion secondary battery comprising the same. The positive plate comprises a positive current collector and a positive coating positioned on at least one side surface of the positive current collector, the positive coating comprises a first positive coating and a second positive coating which are arranged along the thickness direction of the positive plate, and the first positive coating is arranged on at least one side surface of the current collector; the second positive electrode coating is arranged on the surface, deviating from the positive electrode current collector, of the first positive electrode coating; the first positive electrode coating comprises first lithium iron phosphate with an average particle size of 500-1600 nm, and the second positive electrode coating comprises second lithium iron phosphate with an average particle size of 1.6-15 [mu] m; the second lithium iron phosphate includes secondary particles, and the first lithium iron phosphate includes single particles. The positive plate disclosed by the invention is high in energy density and high in Li < + > transmission speed, and the lithium ion secondary battery comprising the positive plate disclosed by the invention has good energy density and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode sheet and a lithium ion secondary battery. Background Art

[0002] With the development of science and technology, lithium-ion secondary batteries are widely used in various electronic devices and electric vehicles due to their advantages such as high energy density, long cycle life and environmental protection. Double-layer coating technology is a commonly used technology in the preparation of lithium-ion batteries, but batteries with double-layer coated pole pieces often have problems such as low energy density and poor cycle performance. Summary of the invention

[0003] The purpose of the present invention is to overcome the above problems existing in the prior art and to provide a lithium ion secondary battery (hereinafter referred to as battery). The positive electrode sheet of the lithium ion secondary battery proposed by the present invention has a first positive electrode coating and a second positive electrode coating stacked in the thickness direction; by controlling the difference between the materials of the first positive electrode coating and the second positive electrode coating and their average particle sizes, the concentration polarization in the diffusion of lithium ions can be improved to ensure that the battery has good energy density, cycle life and stability.

[0004] The inventor of the present invention has found that when the positive electrode coating is controlled to include a first positive electrode coating and a second positive electrode coating stacked along the thickness direction of the positive electrode sheet, the first positive electrode coating is disposed on at least one side surface of the positive electrode current collector, and the second positive electrode coating is disposed on the surface of the first positive electrode coating away from the positive electrode current collector. The first positive electrode coating and the second positive electrode coating respectively include the first lithium iron phosphate and the second lithium iron phosphate with different average particle sizes. When the first positive electrode coating is close to the positive electrode current collector and the second positive electrode coating is away from the positive electrode current collector, the migration path of lithium ions in the electrode is short and the transmission speed is fast, which is conducive to the improvement of energy density, good cycle life and stable performance.

[0005] Based on this, the present invention proposes the following technical solutions:

[0006] A first aspect of the present invention provides a positive electrode sheet, comprising a positive electrode collector and a positive electrode coating located on at least one side of the surface of the positive electrode collector, wherein the positive electrode coating comprises a first positive electrode coating and a second positive electrode coating stacked along the thickness direction of the positive electrode sheet, wherein the first positive electrode coating is arranged on at least one side of the surface of the positive electrode collector, and the second positive electrode coating is arranged on a surface of the first positive electrode coating away from the positive electrode collector; the first positive electrode coating comprises a first lithium iron phosphate, and the second positive electrode coating comprises a second lithium iron phosphate, the first lithium iron phosphate has an average particle size of 500nm-1600nm, and the second lithium iron phosphate has an average particle size of 1.6μm-15μm; the second lithium iron phosphate comprises secondary particles, and the first lithium iron phosphate comprises single particles.

[0007] A second aspect of the present invention provides a lithium ion secondary battery, the lithium ion secondary battery comprising the positive electrode sheet according to the first aspect of the present invention.

[0008] The present invention has at least the following beneficial effects:

[0009] First, the positive electrode sheet of the present invention adopts a positive electrode double-layer coating technology. By controlling the lithium iron phosphate grain structure and the average particle size and distribution of lithium iron phosphate in the first positive electrode coating and the second positive electrode coating, it can improve the concentration polarization in the lithium ion diffusion process and increase the energy density, thereby ensuring that the battery has good energy density, cycle stability and service life.

[0010] Second, the lithium ion secondary battery of the present invention has good energy density, cycle stability and lifespan. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 FIG. 1 is a cross-sectional scanning electron microscope (SEM) image of a positive electrode sheet in one embodiment of the present invention.

[0012] Figure 2 This is a cross-sectional SEM image of the positive electrode sheet in a comparative example of the present invention.

[0013] Figure 3 This is a cross-sectional SEM image of the positive electrode sheet in a comparative example of the present invention.

[0014] Figure 4 This is a cross-sectional SEM image of the positive electrode sheet in a comparative example of the present invention. DETAILED DESCRIPTION

[0015] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0016] A first aspect of the present invention provides a positive electrode sheet, comprising a positive electrode collector and a positive electrode coating located on at least one side surface of the positive electrode collector, wherein the positive electrode coating comprises a first positive electrode coating and a second positive electrode coating stacked along the thickness direction of the positive electrode sheet, wherein the first positive electrode coating is disposed on at least one side surface of the positive electrode collector, and the second positive electrode coating is disposed on a surface of the first positive electrode coating that is away from the positive electrode collector.

[0017] In the present invention, the first positive electrode coating includes a first lithium iron phosphate, the second positive electrode coating includes a second lithium iron phosphate, and the average particle size of the first lithium iron phosphate is 500nm-1600nm, for example, 500nm, 510nm, 520nm, 530nm, 540nm, 550nm, 560nm, 570nm, 580nm, 590nm, 600nm, 620nm, 640nm, 660nm, 680nm, 700nm, 740nm, 780nm, 820nm, 860nm m, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm or 1600nm; the average particle size of the second lithium iron phosphate is 1.6μm-15μm, for example, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm.

[0018] In one embodiment, the average particle size of the first lithium iron phosphate is 700 nm-1500 nm, and the average particle size of the second lithium iron phosphate is 2 μm-10 μm.

[0019] like Figure 1 The figure shows a cross-sectional SEM image of the positive electrode sheet in one embodiment of the present invention. It can be seen from the figure that there are double-layer positive electrode coatings on both sides of the positive electrode collector, and the positive electrode coating on one side of the positive electrode collector is provided with a first positive electrode coating (including a first lithium iron phosphate with a small average particle size) and a second positive electrode coating (including a second lithium iron phosphate with a large average particle size) along the thickness direction.

[0020] In the present invention, along the thickness direction of the positive electrode current collector, a second positive electrode coating including a second lithium iron phosphate and a first positive electrode coating including a first lithium iron phosphate are stacked, and the difference between the average particle sizes of the second lithium iron phosphate and the first lithium iron phosphate is regulated, wherein the first lithium iron phosphate is close to the positive electrode current collector, and the average particle size is small and the compaction density is high, which helps to improve the energy density, while the second lithium iron phosphate is away from the positive electrode current collector, and the average particle size is large, which reduces the lithium ion concentration polarization generated by internal diffusion, improves the lithium ion transmission efficiency, and is beneficial to the cold start of the lithium ion battery. Using different lithium iron phosphates in the first positive electrode coating and the second positive electrode coating can better control the difference between the materials in the first positive electrode coating and the second positive electrode coating, thereby ensuring the cycle stability and life of the battery, balancing the high and low temperature performance of the lithium ion secondary battery, and enhancing the high temperature storage capacity; the differentiated arrangement of the first lithium iron phosphate and the second lithium iron phosphate can effectively avoid the problem of poor battery stability caused by the difference in average particle size, thereby reducing the concentration polarization in lithium ion diffusion, and improving the battery energy density, cycle stability and service life.

[0021] If a single-layer coating is used instead of a double-layer coating, and the first lithium iron phosphate and the second lithium iron phosphate are directly mixed and then evenly coated, the first lithium iron phosphate will be tightly coated on the surface of the second lithium iron phosphate, hindering the contact between the positive electrode conductive agent and the second lithium iron phosphate, increasing the contact impedance, which not only leads to a decrease in the transmission speed of lithium ions in the positive electrode sheet, but also reduces the energy density and cold start performance, which is not conducive to the cycle performance of the battery.

[0022] In the present invention, the ratio of the vertical distance from the second lithium iron phosphate to the positive electrode current collector to the thickness of the positive electrode coating is 1:(1.2-12), for example, 1:1.2, 1:1.25, 1:3, 1:1.35, 1:4, 1:1.45, 1:5, 1:1.55, 1:6, 1:1.65, 1:7, 1:1.75, 1:8, 1:1.85, 1:9, 1:10, 1:11 or 1:12.

[0023] In one embodiment, the ratio of the vertical distance from the second lithium iron phosphate to the positive electrode current collector to the thickness of the positive electrode coating is 1:(1.5-8).

[0024] In the present invention, the kinetic performance of the battery is improved by regulating the ratio of the vertical distance from the second lithium iron phosphate to the positive electrode collector in the second positive electrode coating to the thickness of the positive electrode coating, so that the energy density and cycle performance of the battery are further improved; when the ratio of the vertical distance from the second lithium iron phosphate to the positive electrode collector to the thickness of the positive electrode coating is adjusted to be greater than 1:1.2, the compaction density during coating or rolling is too small, resulting in too low energy density; and when the ratio of the vertical distance from the second lithium iron phosphate to the positive electrode collector to the thickness of the positive electrode coating is adjusted to be less than 1:12, the second lithium iron phosphate is too close to the positive electrode collector under extrusion, resulting in an increase in the contact internal resistance, which deteriorates the cold start performance and cycle performance.

[0025] In the present invention, the vertical distance from the second lithium iron phosphate to the positive electrode current collector is measured by the following method: laser cutting the positive electrode sheet, imaging the obtained cross section using a scanning electron microscope (SEM), selecting at least 10 different second lithium iron phosphates on the obtained electron microscope image, measuring the shortest distance from the boundary of the second lithium iron phosphate to the positive electrode current collector using image analysis software, and then taking the average value as the vertical distance from the second lithium iron phosphate to the positive electrode current collector.

[0026] In the present invention, the thickness of the positive electrode coating can be obtained by conventional testing methods in the art, such as vertically cutting the negative electrode sheet along the thickness direction to obtain a cross section, imaging the obtained cross section by scanning electron microscopy (SEM), and measuring the coating thickness by image analysis software; the average particle size of the first lithium iron phosphate and the second lithium iron phosphate can be obtained by conventional testing methods in the art, such as first obtaining a high-resolution image by scanning electron microscopy, and then performing particle size measurement and distribution statistics by electron microscope image analysis software such as ImageJ to obtain the average particle size, or by laser diffraction testing, and the Dv50 data obtained by the test is the average particle size.

[0027] In the present invention, the second lithium iron phosphate includes secondary particles, and the first lithium iron phosphate includes a single particle.

[0028] In the present invention, the secondary particles include a plurality of primary particles.

[0029] In the present invention, the "secondary particles" are lithium iron phosphate particles with a larger average particle size formed by agglomeration of a number of "primary particles". The "primary particles" are lithium iron phosphate particles with a small average particle size and easy to agglomerate. The "several" means that the number of the primary particles forming the secondary particles is greater than or equal to 2. The "single particle" is a lithium iron phosphate particle with a larger average particle size and not easy to agglomerate.

[0030] In the present invention, the ratio of the average particle size of the primary particles to the average particle size of the first lithium iron phosphate is 1:(1.25-40), for example, 1:1.25, 1:1.3, 1:1.35, 1:1.4, 1:1.45, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:16, 1:18, 1:20, 1:24, 1:28, 1:32, 1:36 or 1:40.

[0031] In one embodiment, the ratio of the average particle size of the primary particles to the average particle size of the first lithium iron phosphate is 1:(2.33-10).

[0032] In the present invention, the positive electrode adopts double-layer coating, and the second lithium iron phosphate located in the second positive electrode coating includes secondary particles formed by a plurality of primary particles. The primary particles are lithium iron phosphate particles with a smaller average particle size and easy to agglomerate. By regulating the ratio of the average particle size of the primary particles and the first lithium iron phosphate located in the first positive electrode coating, the average particle size of the primary particles in the second positive electrode coating and the average particle size of the first lithium iron phosphate in the first positive electrode coating can be within a suitable range and matched with each other, which can not only improve the compaction density of the double-layer coating and avoid excessive agglomeration of the primary particles, but also shorten the diffusion and migration paths of lithium ions in each coating, thereby improving the transmission rate and energy density of the battery.

[0033] When the ratio of the average particle size of the primary particles to the average particle size of the first lithium iron phosphate is greater than 1:1.25, the average particle size of the first lithium iron phosphate is too small and densely packed, and the contact internal resistance is increased due to insufficient conductive network, thereby reducing the cycle capacity; when the ratio of the average particle size of the primary particles to the average particle size of the first lithium iron phosphate is less than 1:40, the average particle size of the primary particles agglomerated into the second lithium iron phosphate is too small, resulting in excessive agglomeration, which reduces the compaction efficiency, and the average particle size of the first lithium iron phosphate is too large, which increases the diffusion and migration path of lithium ions in the lithium iron phosphate, reduces the battery capacity, and affects the energy density of the battery; when lithium ions diffuse on the surface and inside of the first lithium iron phosphate with a larger average particle size, higher concentration polarization is generated, which reduces the battery voltage and is not conducive to cold start performance.

[0034] In the present invention, the average particle size of the primary particles is 50nm-400nm, for example, 50nm, 52nm, 54nm, 56nm, 60nm, 64nm, 68nm, 72nm, 76nm, 80nm, 85nm, 90nm, 95nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 240nm, 280nm, 320nm, 360nm or 400nm.

[0035] In one embodiment, the average particle size of the primary particles is 150nm-300nm.

[0036] In the present invention, the positional relationship of the first positive electrode coating and the second positive electrode coating relative to the positive electrode current collector is also related to the average particle size of the first lithium iron phosphate and the second lithium iron phosphate; when the second positive electrode coating is away from the positive electrode current collector and the first coating is close to the positive electrode current collector, the average particle size of the first lithium iron phosphate is larger than that of the primary particles, resulting in a longer diffusion path of lithium ions in the first lithium iron phosphate, and although the primary particles have a smaller average particle size, they are arranged close to the positive electrode current collector, so that the escaped lithium ions have a longer migration path in the electrode, which increases the diffusion impedance and has a large concentration polarization, further increases the internal resistance of the battery, reduces the terminal voltage of low-temperature and high-rate discharge, and has an adverse effect on the energy density and cold start performance.

[0037] In the present invention, the average particle size of the primary particles can be obtained by conventional testing methods in the art, for example, the same as the testing method for the average particle size of the first lithium iron phosphate and the second lithium iron phosphate, or can be obtained by other conventional testing methods.

[0038] In the present invention, the first positive electrode coating further includes a first positive electrode conductor, and the second positive electrode coating further includes a second positive electrode conductor; the mass content of the second positive electrode conductor in the second positive electrode coating is ≤ the mass content of the first positive electrode conductor in the first positive electrode coating.

[0039] In the present invention, the ratio of the mass content of the second positive electrode conductor in the second positive electrode coating to the mass content of the first positive electrode conductor in the first positive electrode coating is 1:(1-6), for example, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.4, 1:2.8, 1:3.2, 1:3.6, 1:4, 1:4.5, 1:5, 1:5.5, or 1:6.

[0040] In one embodiment, the ratio of the mass content of the second positive electrode conductive agent in the second positive electrode coating to the mass content of the first positive electrode conductive agent in the first positive electrode coating is 1:(1.05-2.75).

[0041] In the present invention, the mass content of the first positive electrode conductor in the first positive electrode coating is 3.9%-6%, for example, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9% or 6%.

[0042] In one embodiment, the mass content of the first positive electrode conductive agent in the first positive electrode coating is 4%-5.5%.

[0043] In the present invention, the mass content of the second positive electrode conductor in the second positive electrode coating is 1%-3.9%, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8% or 3.9%.

[0044] In one embodiment, the mass content of the second positive electrode conductive agent in the second positive electrode coating is 2%-3.8%.

[0045] In the present invention, according to the composition of the first positive electrode coating and the second positive electrode coating and the average particle size of lithium iron phosphate, the mass content and the ratio of the first positive electrode conductive agent and the second positive electrode conductive agent are regulated, so that more conductive pathways can be formed between the first positive electrode coating and the second positive electrode coating, the electron transfer resistance can be reduced, a good conductive network can be constructed, the cold start performance and cycle stability of the battery can be improved, the conductivity of the first positive electrode coating and the second positive electrode coating can be matched, and a large difference can be avoided to affect the conduction of ions in the positive electrode coating. When the ratio of the mass content of the second positive electrode conductive agent in the second positive electrode coating to the mass content of the first positive electrode conductive agent in the first positive electrode coating is less than 1:6, the second positive electrode conductive agent is too little or the first positive electrode conductive agent is too much. At this time, too few conductive channels are formed in the second positive electrode coating. Due to the large particle size of the second lithium iron phosphate, the diffusion path of lithium ions therein is long. Too few conductive channels will hinder the transmission of lithium ions and cause excessive accumulation inside the electrode to cause side reactions, reduce the battery capacity, and affect the battery energy density and life; and when the ratio of the mass content of the second positive electrode conductive agent in the second positive electrode coating to the mass content of the first positive electrode conductive agent in the first positive electrode coating is greater than 1:1, the second positive electrode conductive agent is too much or the first positive electrode conductive agent is too little, the contact resistance between the positive electrode coating and the positive current collector increases, and the electron transmission resistance of the positive electrode sheet is too high, affecting the cold start and cycle performance of the battery.

[0046] In the present invention, the ratio of the thickness of the first positive electrode coating to the second positive electrode coating is 1:(0.11-9.5), for example, 1:0.11, 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:7, 1:8, 1:9 or 1:9.5.

[0047] In one embodiment, the ratio of the thickness of the first positive electrode coating layer to the thickness of the second positive electrode coating layer is 1:(0.23-7).

[0048] In the present invention, the thickness of the first positive electrode coating is 5μm-90μm, for example, 5μm, 6.5μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 60μm, 70μm, 80μm or 90μm; the thickness of the second positive electrode coating is 5μm-90μm, for example, 5μm, 6.5μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 60μm, 70μm, 80μm or 90μm.

[0049] In the present invention, the thickness of the first positive electrode coating and the second positive electrode coating can be measured by conventional testing methods in the art, for example, the positive electrode sheet is cut in the thickness direction, the obtained cross section is imaged by a scanning electron microscope (SEM), the second lithium iron phosphate closest to the current collector is selected on the obtained scanning electron microscope image, and the vertical distance from the lowest point of the second lithium iron phosphate (i.e., the position closest to the positive electrode current collector) to the surface of the second positive electrode coating on this side is measured by image analysis software to obtain the thickness of the second positive electrode coating; the first lithium iron phosphate farthest from the current collector is selected on the obtained scanning electron microscope image, and the vertical distance from the highest point of the first lithium iron phosphate (i.e., the position farthest from the positive electrode current collector) to the surface of the positive electrode current collector on this side is measured by image analysis software to obtain the thickness of the first positive electrode coating.

[0050] In the present invention, the ratio of the average particle size of the second lithium iron phosphate to the thickness of the positive electrode coating on any side of the positive electrode current collector is 1:(1.6-85), for example, 1:1.6, 1:1.7, 1:1.8, 1:2, 1:2.25, 1:2.5, 1:2.75, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:60, 1:70, 1:80 or 1:85.

[0051] In one embodiment, the ratio of the average particle size of the second lithium iron phosphate to the thickness of the positive electrode coating on either side of the positive electrode current collector is 1:(5-37).

[0052] The thickness of the positive electrode coating on either side of the positive electrode current collector is 25μm-130μm, for example, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 110μm, 120μm or 130μm.

[0053] In one embodiment, the thickness of the positive electrode coating on either side of the positive electrode current collector is 55 μm-80 μm.

[0054] In the present invention, since the positive electrode sheet adopts double-layer coating and the average particle size of the lithium iron phosphate particles in the first positive electrode coating and the second positive electrode coating is significantly different, if the thickness of the positive electrode coating and the average particle size are difficult to match, concentration polarization and coating scratches will be caused. Therefore, the inventors thought of improving the coating scratch problem and the concentration polarization problem caused by lithium ion insertion and extraction by regulating the relationship between the average particle size of the second lithium iron phosphate and the thickness of the positive electrode coating on either side of the positive electrode current collector, thereby improving the charging and discharging efficiency of the battery. When the ratio of the average particle size of the second lithium iron phosphate to the thickness of the positive electrode coating on either side of the positive electrode current collector is less than 1:85, the average particle size of the second lithium iron phosphate is too small and the thickness of the positive electrode coating on either side of the positive electrode current collector is too large, resulting in extended lithium ion embedding and extraction paths, resulting in a larger lithium ion concentration gradient and increased concentration polarization, affecting the cold start performance of the battery; and when the ratio of the average particle size of the second lithium iron phosphate to the thickness of the positive electrode coating on either side of the positive electrode current collector is greater than 1:1.6, the particle size of the second lithium iron phosphate is larger and the thickness of the positive electrode coating on either side of the positive electrode current collector is too thin, forming coating scratches, resulting in low coating amount, further affecting the battery capacity, reducing energy density and deteriorating cycle performance.

[0055] In the present invention, the porosity of the positive electrode sheet is 25%-60%, for example, 25%, 26%, 27%, 28%, 29%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58% or 60%.

[0056] In one embodiment, the porosity of the positive electrode sheet is 30%-50%.

[0057] In the present invention, due to the double-layer coating structure, the porosity of the positive electrode sheet will be affected by the first positive electrode coating and the second positive electrode coating. By regulating the porosity of the positive electrode sheet within a certain range, the electrolyte can be promoted to wet the positive electrode active material, improve the lithium ion transmission efficiency and thus improve the battery performance. The adjustment of the porosity of the positive electrode sheet can be achieved by adjusting the thickness ratio of the first positive electrode coating and the second positive electrode coating or by adjusting the distance from the second lithium iron phosphate to the positive electrode current collector. When the porosity of the positive electrode sheet is less than 25%, it is difficult for the electrolyte to fill the electrode pores alone, resulting in insufficient electrolyte infiltration, slow lithium ion transmission speed, and weakened energy density and cold start capability; and when the porosity of the positive electrode sheet is greater than 60%, the conduction speed of lithium ions through the electrolyte in the pores is too fast, forming lithium dendrites and increasing the self-discharge of the battery.

[0058] In the present invention, the porosity of the positive electrode sheet can be obtained by conventional testing methods in the art, such as disassembling the battery in a dry environment, separating the positive electrode sheet, soaking the positive electrode sheet with dimethyl carbonate for at least 3 times, each soaking time is not less than 30 minutes, and then placing it in a blast oven for drying; measuring the length, width and thickness of the positive electrode sheet; weighing the mass of the positive electrode sheet with an analytical balance, winding it and placing it in a sample cup for true density testing, and calculating the porosity.

[0059] In the present invention, the sphericity of the second lithium iron phosphate is 0.2-1, for example, 0.22, 0.24, 0.26, 0.28, 0.3, 0.34, 0.38, 0.42, 0.46, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.9 or 1.

[0060] In one embodiment, the sphericity of the second lithium iron phosphate is 0.6-1.

[0061] In the present invention, the second lithium iron phosphate is a spherical particle, and the sphericity is the ratio of the short axis diameter to the long axis diameter of the sphere. When the sphericity of the second lithium iron phosphate is less than 0.2, the contact between the second lithium iron phosphates is too large, resulting in an increase in the contact internal resistance of the second lithium iron phosphate and affecting the conductive path of the second positive electrode coating where it is located, thereby weakening the battery's cycle performance and cold start performance.

[0062] In the present invention, the sphericity of the second lithium iron phosphate can be tested by conventional methods in the art, for example, after discharging the battery to 0% SOC, disassembling and removing the positive electrode sheet, soaking it in dimethyl carbonate (DMC) solvent for 12 hours, rinsing it with DMC solvent to remove the lithium salt attached to the positive electrode sheet, and then washing the second positive electrode coating from the positive electrode current collector with deionized water, centrifuging to remove the filtrate after ultrasonication, drying, and observing the obtained powder with SEM. Image analysis is performed on the second lithium iron phosphate particles in the SEM mirror image at a certain magnification (for example, 2000 times) by image processing software (such as Image Pro Plus), at least 10 second lithium iron phosphate particles in the mirror image are selected, and the major axis diameter and minor axis diameter of each particle are obtained, and the sphericity of each particle is calculated, and then the average value is taken.

[0063] In the present invention, the first lithium iron phosphate and the second lithium iron phosphate contain element Ti, the mass content of element Ti in the first lithium iron phosphate is C1, the mass content of element Ti in the second lithium iron phosphate is C2, and the ratio of C2 to C1 is 1:(1.5-50), for example, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:7, 1:10, 1:14, 1:18, 1:22, 1:24, 1:28, 1:32, 1:36, 1:40, 1:45 or 1:50.

[0064] In one embodiment, the ratio of C2 to C1 is 1:(2.78-16).

[0065] In the present invention, C1 is 3000ppm-10000ppm, for example, 3000ppm, 3200ppm, 3400ppm, 3600ppm, 3800ppm, 4000ppm, 4400ppm, 4800ppm, 5200ppm, 5600ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm or 10000ppm; C2 is 200ppm-2000ppm, for example 200ppm, 210ppm, 220ppm, 230ppm, 240ppm, 260ppm, 280ppm, 300ppm, 340ppm, 380ppm, 420ppm, 460ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1200ppm, 1400ppm, 1600ppm, 1800ppm or 2000ppm.

[0066] In one embodiment, C1 is 5000ppm-8000ppm, and C2 is 500ppm-1800ppm.

[0067] In the present invention, in order to enhance the stability of the double-layer coated positive electrode coating, the element Ti is introduced into the first lithium iron phosphate and the second lithium iron phosphate. When the battery is charged, the element Ti can occupy the lithium vacancies in time after the lithium ions are released, which has the function of maintaining the structural stability of the first lithium iron phosphate and the second lithium iron phosphate, and can enhance the stability of the first positive electrode coating and the second positive electrode coating; since the average particle size of the first lithium iron phosphate is larger and the average particle size of the second lithium iron phosphate is smaller, the mass content of the element Ti in the first lithium iron phosphate and the second lithium iron phosphate satisfies C1>C2, so that while keeping C2 small to avoid the risk of self-discharge, C1 can be made larger to fill the second lithium iron phosphate and improve stability.

[0068] When the ratio of C2 to C1 is less than 1:50, the element Ti in the second lithium iron phosphate is too little, resulting in too many lithium vacancies that cannot be filled, affecting the structure of the second lithium iron phosphate. There are not enough sites to accept the embedding of lithium ions during discharge, which weakens the cycle performance of the battery; when the ratio of C2 to C1 is greater than 1:1.5, the element Ti in the first lithium iron phosphate is too little to fill the lithium vacancies, which reduces the structural stability of the first lithium iron phosphate, and too much element Ti in the second lithium iron phosphate is dissolved, which easily forms dendrites and increases the self-discharge ability of the battery.

[0069] In the present invention, the mass content of the element Ti in the first lithium iron phosphate and the second lithium iron phosphate can be measured by conventional testing methods in the art, for example, by inductively coupled plasma atomic emission spectroscopy (ICP-AES).

[0070] A second aspect of the present invention provides a lithium ion secondary battery, the lithium ion secondary battery comprising the positive electrode sheet according to the first aspect of the present invention.

[0071] In the present invention, the lithium-ion secondary battery further includes a negative electrode sheet and a separator.

[0072] In the present invention, the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes hard carbon.

[0073] In the present invention, hard carbon has a high specific surface area and good structural stability. As a negative electrode active material, it has the characteristics of good rate performance and long cycle life, especially showing application advantages under low temperature conditions; and lithium iron phosphate as a positive electrode active material also has the characteristics of good structural stability, long cycle life and high energy density. The two are matched, so that the battery not only shows good rate performance and cycle performance, but also makes it suitable for low temperature conditions and has good cold start performance; further, the double-layer coating design of the positive electrode sheet and the differentiated particle size of lithium iron phosphate in the first positive electrode coating and the second positive electrode coating reduce concentration polarization, improve the energy density of the battery, and enhance the cycle stability and cycle life of the battery.

[0074] In the present invention, the lithium-ion secondary battery includes a rolled core and / or a stacked core.

[0075] In the present invention, the ratio of the average particle size of the negative electrode active material to the thickness of the separator is 1:(0.4-5), for example, 1:0.4, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.4, 1:2.8, 1:3.2, 1:3.6, 1:4, 1:4.5 or 1:5.

[0076] In one embodiment, the ratio of the average particle size of the negative electrode active material to the thickness of the separator is 1:(0.8-3.6).

[0077] In the present invention, the average particle size of the negative electrode active material is 4μm-20μm, for example, 4μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 7.5μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.

[0078] In one embodiment, the average particle size of the negative electrode active material is 5 μm-15 μm.

[0079] In the present invention, the thickness of the diaphragm is 8μm-20μm, for example, 8μm, 8.2μm, 8.4μm, 8.6μm, 8.8μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm, 15.5μm, 16μm, 17μm, 18μm, 19μm or 20μm.

[0080] In one embodiment, the thickness of the diaphragm is 12 μm-18 μm.

[0081] In the present invention, the separator may be a conventional one in the art.

[0082] In the present invention, regulating the ratio of the average particle size of the negative electrode active material to the thickness of the separator plays an important role in regulating the transmission speed of lithium ions and increasing the capacity and energy density. When the ratio of the average particle size of the negative electrode active material to the thickness of the diaphragm is less than 1:5, the average particle size of the negative electrode active material is too small or the thickness of the diaphragm is too large. The excessive thickness of the diaphragm will increase the transmission path of lithium ions, resulting in an increase in the internal resistance of the battery, thereby deteriorating the cold start and cycle capabilities. If the average particle size of the negative electrode active material is too small, more lithium ions will be consumed when forming the SEI film, increasing the irreversible capacity loss, and further reducing the energy density and the capacity retention rate during storage. When the ratio of the average particle size of the negative electrode active material to the thickness of the diaphragm is greater than 1:0.4, the average particle size of the negative electrode active material is too large or the thickness of the diaphragm is too small. If the thickness of the diaphragm is too small, lithium ions will pass through quickly during charging and deposit excessively on the negative electrode side, forming lithium dendrites to increase self-discharge. At this time, the average particle size of the negative electrode active material is too large, which increases the contact area between the diaphragm and the negative electrode sheet, causing lithium ions to be unevenly distributed on the surface of the negative electrode active material, resulting in lithium precipitation, which is not conducive to improving the battery energy density, cycle stability and life.

[0083] In the present invention, the average particle size of the negative electrode active material can be obtained by conventional testing methods in the art, such as imaging using a scanning electron microscope, and the testing method is the same as the testing method for the average particle size of the first lithium iron phosphate and the second lithium iron phosphate; the thickness of the diaphragm can be obtained by conventional testing methods in the art, such as imaging the obtained cross-section using a scanning electron microscope (SEM) and measuring the thickness of the diaphragm using image analysis software.

[0084] In the present invention, the first positive electrode conductive agent and the second positive electrode conductive agent are each independently selected from at least one of acetylene black, conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene.

[0085] In the present invention, the positive electrode sheet further includes a positive electrode binder, and the negative electrode sheet further includes a negative electrode conductive agent and a negative electrode binder, and the positive electrode conductive agent, the positive electrode binder, the negative electrode conductive agent and the negative electrode binder are all conventionally selected in the art. For example, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), polyacrylate, polyimide and styrene-butadiene rubber, the negative electrode binder includes at least one of polyacrylic acid (PAA), sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, polyimide, styrene-butadiene rubber (SBR) and polyvinylidene fluoride, and the negative electrode conductive agent includes at least one of acetylene black, conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene.

[0086] In the present invention, the lithium-ion secondary battery further includes an electrolyte or an electrolyte, and the electrolyte or the electrolyte can be a conventional choice in the art.

[0087] The lithium ion secondary battery of the present invention is suitable for automotive power batteries and has good performance, performance stability and lifespan.

[0088] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0089] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0090] In the following examples, unless otherwise specified, all materials used were commercially available of analytical grade.

[0091] In the following embodiments, the average particle size of the first lithium iron phosphate is recorded as d1, the average particle size of the second lithium iron phosphate is recorded as d2, the average particle size of the primary particles is recorded as d0, the thickness of the positive electrode coating on one side of the current collector (i.e., the single-sided positive electrode coating) is recorded as L, the thickness of the first positive electrode coating is recorded as L1, and the thickness of the second positive electrode coating is recorded as L2; ​​the mass content of the first positive electrode conductor in the first positive electrode coating is recorded as w1, the mass content of the second positive electrode conductor in the second positive electrode coating is recorded as w2, and the vertical distance from the second lithium iron phosphate to the positive current collector is recorded as x1.

[0092] Embodiment 1:

[0093] (1) Preparation of positive electrode

[0094] A first lithium iron phosphate (whose average particle size is denoted as d1, d1 is 1150 nm, and the mass content of element Ti in the first lithium iron phosphate is C1, C1 is 6840.4 ppm), PVDF and a first positive electrode conductor (conductive carbon black SP1, whose mass content in the first positive electrode coating is w1, w1 is 5.2%) are stirred and mixed to form a uniform and stable mixture to obtain a first positive electrode slurry, wherein the solid component contains 92 wt% of the first lithium iron phosphate, 3.5 wt% of PVDF and 4.5 wt% of the conductive carbon black SP2, and the solvent is N-methylpyrrolidone (NMP);

[0095] A second lithium iron phosphate (whose average particle size is denoted as d2, d2 is 5.1 μm, sphericity is 1, and the mass content of element Ti in the second lithium iron phosphate is C2, C2 is 684.3 ppm), PVDF and a second positive electrode conductor (conductive carbon black SP2, whose mass content in the first positive electrode coating is w2, w2 is 2.6%) are stirred and mixed to form a uniform and stable mixture to obtain a second positive electrode slurry, wherein the solid component comprises 93.5 wt% of the second lithium iron phosphate, 3.5 wt% of PVDF and 3 wt% of the conductive carbon black SP1, the solvent is NMP, the second lithium iron phosphate comprises a plurality of primary particles (whose average particle size is denoted as d0, d0 is 209 nm), and the ratio of the average particle size of the primary particles to the average particle size of the first lithium iron phosphate (denoted as d0:d1) is 1:5.5;

[0096] The second positive electrode slurry is applied on the upper layer and the first positive electrode slurry is applied on the lower layer. The surface density ratio of the second positive electrode slurry to the first positive electrode slurry is 1:4.5. The second positive electrode slurry is evenly applied on both sides of the aluminum foil. After drying and roller pressing, the positive electrode sheet is obtained.

[0097] At this time, the ratio of the vertical distance from the second lithium iron phosphate to the positive electrode collector (denoted as x1) to the thickness of the single-sided positive electrode coating (denoted as L) x1:L is 1:6.25, x1=9.6μm, L=60μm; the ratio of the average particle size of the second lithium iron phosphate to the thickness of the single-sided positive electrode coating d2:L is 1:11.76; the ratio of the thickness of the first positive electrode coating to the second positive electrode coating (denoted as L1:L2) is 1:4.5; the ratio of the mass content of the second positive electrode conductor in the second positive electrode coating to the mass content of the first positive electrode conductor in the first positive electrode coating (denoted as w2:w1) is 1:2; the mass content of elemental Ti in the second lithium iron phosphate and the mass content of elemental Ti in the first lithium iron phosphate (denoted as C2:C1) are 1:10; the porosity of the positive electrode sheet is 40.56%.

[0098] (2) Preparation of negative electrode sheet

[0099] The negative electrode active material (90% graphite + 10% hard carbon, with an average particle size of 10μm), SBR and conductive agent conductive carbon black E1 are mixed, and a uniform and stable negative electrode slurry (solid content is 46wt%) is formed by stirring, wherein the solid component contains 95wt% of the negative electrode active material, 3wt% of SBR, 2wt% of the conductive agent E1, and the solvent is water; the negative electrode slurry is evenly applied on both sides of the copper foil, and after drying and roller pressing, a negative electrode sheet is obtained.

[0100] (3) Assembly of lithium-ion secondary batteries

[0101] The obtained positive and negative electrode sheets are wound / stacked to form a bare battery cell, and the aluminum tabs and copper-plated nickel tabs are welded after hot pressing; the aluminum plastic film is punched and packaged, and then vacuum-baked at 95°C for 24 hours; the electrolyte uses a 1M lithium hexafluorophosphate electrolyte, and the solvent is a mixed solvent of ethylene carbonate: dimethyl carbonate: 1,2-propylene glycol carbonate with a volume ratio of 1:1:1. After injection, the battery is formed, sealed, sorted, and OCV tested to obtain a soft-package battery.

[0102] At this time, the ratio of the average particle size of the negative electrode active material to the thickness of the separator was 1:1.5, and the thickness of the separator was 15 μm.

[0103] Embodiment 2:

[0104] (1) Preparation of positive electrode

[0105] A first lithium iron phosphate (d1 is 703 nm, C1 is 5023.2 ppm), PVDF and a first positive electrode conductor (conductive carbon black SP1, w1 is 4%) are stirred and mixed to form a uniform and stable mixture to obtain a first positive electrode slurry, wherein the solid component contains 92 wt% of the first lithium iron phosphate, 3.5 wt% of PVDF and 4.5 wt% of the conductive carbon black SP2, and the solvent is NMP;

[0106] A second lithium iron phosphate (d2 is 10 μm, sphericity is 0.6, C2 is 1807.1 ppm), PVDF and a second positive electrode conductor (conductive carbon black SP2, w2 is 3.8%) are stirred and mixed to form a uniform and stable mixture to obtain a second positive electrode slurry, wherein the solid component contains 93.5 wt% of the second lithium iron phosphate, 3.5 wt% of PVDF and 3 wt% of the conductive carbon black SP1, the solvent is NMP, and the second lithium iron phosphate contains a plurality of primary particles (d0 is 297 nm), and d0:d1 is 1:2.37;

[0107] The second positive electrode slurry is applied on the upper layer and the first positive electrode slurry is applied on the lower layer. The surface density ratio of the second positive electrode slurry to the first positive electrode slurry is 1:7. The second positive electrode slurry is evenly applied on both sides of the aluminum foil, and the positive electrode sheet is obtained after drying and roller pressing.

[0108] At this time, x1:L is 1:8, x1=6.9μm, L=55μm; d2:L is 1:5.5, L1:L2 is 1:7; w2:w1 is 1:1.05; C2:C1 is 1:2.78; the porosity of the positive electrode sheet is 49.17%.

[0109] (2) Preparation of negative electrode sheet

[0110] The negative electrode active material (80% graphite + 20% hard carbon, with an average particle size of 15μm), SBR and conductive agent conductive carbon black E1 are mixed, and a uniform and stable negative electrode slurry (solid content is 46wt%) is formed by stirring, wherein the solid component contains 95wt% of the negative electrode active material, 3wt% of SBR, 2wt% of the conductive agent E1, and the solvent is water; the negative electrode slurry is evenly applied on both sides of the copper foil, and after drying and roller pressing, a negative electrode sheet is obtained.

[0111] (3) Assembly of lithium-ion secondary batteries

[0112] The obtained positive and negative electrode sheets are wound / stacked to form a bare battery cell, and the aluminum tabs and copper-plated nickel tabs are welded after hot pressing; the aluminum plastic film is punched and packaged, and then vacuum-baked at 95°C for 24 hours; the electrolyte uses a 1M lithium hexafluorophosphate electrolyte, and the solvent is a mixed solvent of ethylene carbonate: dimethyl carbonate: 1,2-propylene glycol carbonate with a volume ratio of 1:1:1. After injection, the battery is formed, sealed, sorted, and OCV tested to obtain a soft-package battery.

[0113] At this time, the ratio of the average particle size of the negative electrode active material to the thickness of the separator was 1:0.8, and the thickness of the separator was 12 μm.

[0114] Embodiment 3:

[0115] (1) Preparation of positive electrode

[0116] A first lithium iron phosphate (d1 is 1496nm, C1 is 8000.9ppm), PVDF and a first positive electrode conductor (conductive carbon black SP1, w1 is 5.5%) are stirred and mixed to form a uniform and stable mixture to obtain a first positive electrode slurry, wherein the solid component contains 92wt% of the first lithium iron phosphate, 3.5wt% of PVDF and 4.5wt% of the conductive carbon black SP2, and the solvent is NMP;

[0117] A second lithium iron phosphate (d2 is 2.2 μm, sphericity is 0.8, C2 is 500.8 ppm), PVDF and a second positive electrode conductive agent (conductive carbon black SP2, w2 is 2%) are stirred and mixed to form a uniform and stable mixture to obtain a second positive electrode slurry, wherein the solid component contains 93.5 wt% of the second lithium iron phosphate, 3.5 wt% of PVDF and 3 wt% of the conductive carbon black SP1, the solvent is NMP, and the second lithium iron phosphate contains a plurality of primary particles (d0 is 151 nm), and d0:d1 is 1:9.91;

[0118] The second positive electrode slurry is applied on the upper layer and the first positive electrode slurry is applied on the lower layer. The surface density ratio of the second positive electrode slurry to the first positive electrode slurry is 1:0.23. The second positive electrode slurry is evenly applied on both sides of the aluminum foil, and the positive electrode sheet is obtained after drying and roller pressing.

[0119] At this time, x1:L is 1:2, x1=40μm, L=80μm; d2:L is 1:36.36, L1:L2 is 1:0.23; w2:w1 is 1:2.75; C2:C1 is 1:16; the porosity of the positive electrode sheet is 30.28%.

[0120] (2) Preparation of negative electrode sheet

[0121] The negative electrode active material (85% graphite + 15% hard carbon, with an average particle size of 5 μm), SBR and conductive agent conductive carbon black E1 are mixed, and a uniform and stable negative electrode slurry (solid content is 46wt%) is formed by stirring and mixing, wherein the solid component contains 95wt% of the negative electrode active material, 3wt% of SBR, 2wt% of the conductive agent E1, and the solvent is water; the negative electrode slurry is evenly applied on both sides of the copper foil, and after drying and roller pressing, a negative electrode sheet is obtained.

[0122] (3) Assembly of lithium-ion secondary batteries

[0123] The obtained positive and negative electrode sheets are wound / stacked to form a bare battery cell, and the aluminum tabs and copper-plated nickel tabs are welded after hot pressing; the aluminum plastic film is punched and packaged, and then vacuum-baked at 95°C for 24 hours; the electrolyte uses a 1M lithium hexafluorophosphate electrolyte, and the solvent is a mixed solvent of ethylene carbonate: dimethyl carbonate: 1,2-propylene glycol carbonate with a volume ratio of 1:1:1. After injection, the battery is formed, sealed, sorted, and OCV tested to obtain a soft-package battery.

[0124] At this time, the ratio of the average particle size of the negative electrode active material to the thickness of the separator was 1:3.6, and the thickness of the separator was 18 μm.

[0125] Embodiment 4:

[0126] (1) Preparation of positive electrode

[0127] A first lithium iron phosphate (d1 is 1328 nm, C1 is 7410.3 ppm), PVDF and a first positive electrode conductor (conductive carbon black SP1, w1 is 5.5%) are stirred and mixed to form a uniform and stable mixture to obtain a first positive electrode slurry, wherein the solid component contains 92 wt% of the first lithium iron phosphate, 3.5 wt% of PVDF and 4.5 wt% of the conductive carbon black SP2, and the solvent is NMP;

[0128] A second lithium iron phosphate (d2 is 5.9 μm, sphericity is 1, C2 is 1235.2 ppm), PVDF and a second positive electrode conductive agent (conductive carbon black SP2, w2 is 2%) are stirred and mixed to form a uniform and stable mixture to obtain a second positive electrode slurry, wherein the solid component contains 93.5 wt% of the second lithium iron phosphate, 3.5 wt% of PVDF and 3 wt% of the conductive carbon black SP1, the solvent is NMP, and the second lithium iron phosphate contains a plurality of primary particles (d0 is 162 nm), and d0:d1 is 1:8.2;

[0129] The second positive electrode slurry is applied on the upper layer and the first positive electrode slurry is applied on the lower layer. The surface density ratio of the second positive electrode slurry to the first positive electrode slurry is 1:0.4. The second positive electrode slurry is evenly applied on both sides of the aluminum foil. After drying and roller pressing, the positive electrode sheet is obtained.

[0130] At this time, x1:L is 1:1.5, x1=46.7μm, L=70μm; d2:L is 1:11.86, L1:L2 is 1:0.4; w2:w1 is 1:2.75; C2:C1 is 1:6; the porosity of the positive electrode sheet is 32.89%.

[0131] (2) Preparation of negative electrode sheet

[0132] The negative electrode active material (70% graphite + 30% hard carbon, with an average particle size of 5 μm), SBR and conductive agent conductive carbon black E1 are mixed, and a uniform and stable negative electrode slurry (solid content is 46wt%) is formed by stirring, wherein the solid component contains 95wt% of the negative electrode active material, 3wt% of SBR, 2wt% of the conductive agent E1, and the solvent is water; the negative electrode slurry is evenly applied on both sides of the copper foil, and after drying and roller pressing, a negative electrode sheet is obtained.

[0133] (3) Assembly of lithium-ion secondary batteries

[0134] The obtained positive and negative electrode sheets are wound / stacked to form a bare battery cell, and the aluminum tabs and copper-plated nickel tabs are welded after hot pressing; the aluminum plastic film is punched and packaged, and then vacuum-baked at 95°C for 24 hours; the electrolyte uses a 1M lithium hexafluorophosphate electrolyte, and the solvent is a mixed solvent of ethylene carbonate: dimethyl carbonate: 1,2-propylene glycol carbonate with a volume ratio of 1:1:1. After injection, the battery is formed, sealed, sorted, and OCV tested to obtain a soft-package battery.

[0135] At this time, the ratio of the average particle size of the negative electrode active material to the thickness of the separator was 1:3.6, and the thickness of the separator was 18 μm.

[0136] Embodiment 5 group:

[0137] This group of examples is used to verify the influence of "the ratio of the vertical distance (x1) from the second lithium iron phosphate to the positive electrode current collector to the thickness (L) of the single-sided positive electrode coating", i.e. "x1:L", by keeping L unchanged and adjusting the surface density and compaction density of the first positive electrode coating and the second positive electrode coating, as follows:

[0138] Example 5a is based on Example 3, except that the positive electrode sheet is different, specifically, x1:L is 1:1.24, x1 is 64.5 μm, and the porosity of the positive electrode sheet is 25.13%.

[0139] Example 5b is based on Example 2, except that the positive electrode sheet is different, specifically, x1:L is 1:11.27, x1 is 4.9 μm, and the porosity of the positive electrode sheet is 36.34%.

[0140] Example 5c is based on Example 3, except that the positive electrode sheet is different, specifically, x1:L is 0, x1 is 0 μm, and the porosity of the positive electrode sheet is 27.34%.

[0141] Embodiment 6 group:

[0142] This group of examples is used to verify the influence of the change of "the ratio of the average particle size of the primary particles to the average particle size of the first lithium iron phosphate", i.e. "d0:d1", by adjusting the average particle size of the first lithium iron phosphate (d1) and the average particle size of the primary particles (d0), as follows:

[0143] Example 6a is based on Example 3, except that d1=505 nm, d0 is 400 nm, and at this time, d0:d1 is 1:1.25, and the porosity of the positive electrode sheet is 28.71%.

[0144] Example 6b is based on Example 3, except that d1=1593 nm, d0 is 50 nm, and at this time, d0:d1 is 1:32, and the porosity of the positive electrode sheet is 31.77%.

[0145] Embodiment 7 group:

[0146] This group of embodiments is used to verify the influence of the change of the "average particle size of the second lithium iron phosphate", i.e., "d2", by adjusting the particle size of the second lithium iron phosphate, as follows:

[0147] Example 7a is based on Example 3, but differs in that d2=1.7 μm. In this case, d2:L is 1:47.06, and the porosity of the positive electrode sheet is 29.08%.

[0148] Example 7b is based on Example 3, but differs in that d2=14.5 μm. In this case, d2:L is 1:5.52, and the porosity of the positive electrode sheet is 34.01%.

[0149] Embodiment 8 group:

[0150] This group of examples is used to verify the influence of the change of "the ratio of the average particle size of the second lithium iron phosphate to the thickness of the single-sided positive electrode coating", namely "d2:L", by adjusting the average particle size of the second lithium iron phosphate and the surface density of the first positive electrode coating and the second positive electrode coating, as follows:

[0151] Example 8a is based on Example 3, except that d2 is 14.9 μm, L is 25.3 μm, and L1:L2 is 1:7; at this time, d2:L is 1:1.7, x1:L is 1:8.16, x1 is 3.1 μm, and the porosity of the positive electrode sheet is 40.9%.

[0152] Example 8b is based on Example 3, except that d2 is 2.2 μm, L is 128 μm, and L1:L2 is 1:0.8; at this time, d2:L is 1:80, x1:L is 1:2.84, x1 is 45 μm, and the porosity of the positive electrode sheet is 30.66%.

[0153] Embodiment 9 group:

[0154] This group of examples is used to verify the influence of the change of "the ratio of the thickness of the first positive electrode coating to the second positive electrode coating", i.e. "L1:L2", by adjusting the surface density of the first positive electrode coating and the surface density of the second positive electrode coating, as follows:

[0155] Example 9a is based on Example 5a, except that L1:L2 is 1:0.15, and the porosity of the positive electrode sheet is 25.2%.

[0156] Example 9b is based on Example 5b, except that L1:L2 is 1:9.5, and the porosity of the positive electrode sheet is 55.65%.

[0157] Example 10 Group:

[0158] This group of examples is used to verify the influence of the change of "the ratio of the mass content of the second positive electrode conductive agent in the second positive electrode coating to the mass content of the first positive electrode conductive agent in the first positive electrode coating", i.e. "w2:w1", by adjusting the amount of the first positive electrode conductive agent and the second positive electrode conductive agent, as follows:

[0159] Example 10a is based on Example 3, except that w1 is 3.9%, w2 is 3.9%, and w2:w1 is 1:1.

[0160] Example 10b is based on Example 3, except that w1 is 5.95%, w2 is 1.02%, and w2:w1 is 1:5.85.

[0161] Embodiment 11:

[0162] Based on Example 3, the difference is that the sphericity of the second lithium iron phosphate is 0.22.

[0163] Embodiment 12 group:

[0164] This group of examples is used to verify the influence of the change of "the ratio of C2 to C1", which is achieved by regulating the mass content of the element Ti in the first lithium iron phosphate and the mass content of the element Ti in the second lithium iron phosphate, as follows:

[0165] Example 12a is based on Example 3, except that C1 is 3080.7 ppm, C2 is 1990.1 ppm, and the ratio of C2 to C1 is 1:1.55.

[0166] Example 12b is based on Example 3, except that C1 is 9991.6 ppm, C2 is 206.4 ppm, and the ratio of C2 to C1 is 1:48.5.

[0167] Embodiment 13 group:

[0168] This group of examples is used to verify the impact of the change in the "ratio of the average particle size of the negative electrode active material to the thickness of the separator", which is achieved by adjusting the average particle size of the negative electrode active material and the thickness of the separator, as follows:

[0169] Example 13a is based on Example 3, except that the average particle size of the negative electrode active material is 19.5 μm, the thickness of the separator is 8.2 μm, and the ratio of the average particle size of the negative electrode active material to the thickness of the separator is 1:0.42.

[0170] Example 13b is based on Example 3, except that the average particle size of the negative electrode active material is 4.1 μm, the thickness of the separator is 19.8 μm, and the ratio of the average particle size of the negative electrode active material to the thickness of the separator is 1:4.85.

[0171] Embodiment 14

[0172] Based on Example 3, the difference is that the negative electrode active material is 100% graphite.

[0173] Comparative Example 1

[0174] Based on Example 3, the difference is that only a single layer of the second positive electrode slurry is coated on the positive electrode sheet to obtain a positive electrode coating with a thickness of 80 μm. At this time, the porosity of the positive electrode sheet is 43.18%.

[0175] like Figure 2 The cross-sectional SEM image of the positive electrode sheet of comparative example 1 of the present invention is shown. It can be seen from the image that when only a single layer of the second positive electrode slurry is coated, the second lithium iron phosphate is distributed in the obtained positive electrode coating.

[0176] Comparative Example 2

[0177] Based on Example 3, the difference is that only a single layer of the first positive electrode slurry is coated on the positive electrode sheet to obtain a positive electrode coating with a thickness of 80 μm. At this time, the porosity of the positive electrode sheet is 28.41%.

[0178] like Figure 3 The cross-sectional SEM image of the positive electrode sheet of Comparative Example 2 of the present invention is shown. It can be seen from the image that when only a single layer of the first positive electrode slurry is coated, the first lithium iron phosphate is distributed in the obtained positive electrode coating.

[0179] Comparative Example 3

[0180] Based on Example 3, the difference is that after the first positive electrode slurry and the second positive electrode slurry are mixed in a ratio of 8:2, a single layer is coated on the surface of the positive electrode sheet to obtain a positive electrode coating with a thickness of 80 μm. At this time, the porosity of the positive electrode sheet is 26.13%.

[0181] like Figure 4 The cross-sectional SEM image of the positive electrode sheet of comparative example 3 of the present invention is shown. It can be seen from the figure that when the first positive electrode slurry and the second positive electrode slurry are mixed into a single layer, the first lithium iron phosphate and the second lithium iron phosphate in the obtained positive electrode coating are difficult to distinguish.

[0182] Comparative Example 4

[0183] Based on Example 3, the difference is that the first positive electrode slurry is coated on the upper layer, and the second positive electrode slurry is coated on the lower layer. At this time, the porosity of the positive electrode sheet is 29.83%.

[0184] In the above embodiments, the thickness L1 of the first positive electrode coating is in the range of 5 μm-90 μm, and the thickness L2 of the second positive electrode coating is in the range of 5 μm-90 μm.

[0185] In the above embodiments, the solid content of the first positive electrode slurry is in the range of 50 wt %-58 wt %, and the solid content of the second positive electrode slurry is in the range of 58 wt %-64 wt %.

[0186] Test example:

[0187] (1) Battery cold start test:

[0188] In an environment of (25±2)℃, discharge at a standard 1C constant current to a discharge termination voltage of 2.2V, and place for 30min; then charge at a standard 1C constant current and constant voltage to a charge limit voltage of 3.65V, with a cutoff current of 0.05C, and place for 30min; discharge at a standard 1C constant current to a discharge termination voltage of 2.2V to obtain the actual capacity C0 of the battery, and place for 30min; charge at a standard 1C constant current and constant voltage to a charge limit voltage of 3.65V, with a cutoff current of 0.05C, and discharge at 1C0 for 30min, which is 50% SOC; after standing at (25±2)℃ for 2h, place the battery in a -28℃ constant temperature box and maintain a constant temperature for 4h; test the terminal voltage value of 3C constant current discharge for 2s, which is the battery cold start terminal voltage, in V.

[0189] (2) Battery cycle test:

[0190] At 25℃, discharge at 3C standard constant current to the discharge termination voltage of 2.2V, and leave it for 30min; then charge at 3C standard constant current and constant voltage to the charge limit voltage of 3.65V, with a cut-off current of 0.05C, and leave it for 30min; discharge at 3C standard constant current to the discharge termination voltage of 2.2V, and leave it for 30min; repeat the above full charge and discharge steps until the capacity decays to 80% and the cut-off is reached. The number of repeated cycles is the cycle number, which is used to evaluate the cycle performance of the battery after aging.

[0191] (3) Energy density test:

[0192] The weight of the lithium-ion battery after the second sealing process is recorded as the battery weight. The energy discharged to 2.2V after being fully charged to 3.65V and standing for 5 minutes in the sorting process is recorded as the discharge energy. The width, height and thickness of the lithium-ion battery are tested after OCV is lowered. The volume of the lithium-ion battery = width × height × thickness; the ratio of the discharge energy to the battery volume is the energy density of the battery, and the unit is Wh / L.

[0193] (4) Battery storage capacity retention rate:

[0194] At (25±2)℃, discharge at 1C standard constant current to the discharge end voltage of 2.2V, and leave it for 30min; then charge at 1C standard constant current and constant voltage to the charge limit voltage of 3.65V, with a cut-off current of 0.05C, and leave it for 30min; discharge at 1C standard constant current to the discharge end voltage of 2.2V, and get the initial capacity C of the battery. 始 , put aside for 30 minutes; charge with 1C standard constant current and constant voltage to the charge limit voltage of 3.65V, the cut-off current is 0.05C, and then put it aside for 30 days in an open circuit environment at 60℃; stand at (25±2)℃ for 1h, discharge with 1C standard constant current to the discharge end voltage of 2.2V, then charge with 1C standard constant current and constant voltage to the charge limit voltage of 3.65V, the cut-off current is 0.05C, and then discharge with 1C standard constant current to the discharge end voltage of 2.2V, and obtain the recovery capacity C 末 ; The battery recovery capacity retention rate is C 末 / C 始 ×100%.

[0195] (5) Self-discharge rate test:

[0196] At (25±2)℃, discharge at 1C standard constant current to the discharge termination voltage of 2.2V, and place it aside for 30min; then charge at 1C standard constant current and constant voltage to the charge limit voltage of 3.65V, with a cut-off current of 0.05C, and place it aside for 30min; discharge at 1C standard constant current to the discharge termination voltage of 2.2V, record the actual capacity of the battery C0, and place it aside for 30min; charge at 1C0 constant current to 36% SOC, then discharge 3% SOC at 1C0, at this time it is 33% SOC, and place it aside for 30min; record the initial voltage OCV1, and after storing at room temperature for 30 days, record the terminal voltage OCV2. Battery self-discharge rate = (OCV1-OCV2) / storage time, in mV / h.

[0197] The performance tests of the batteries obtained in the examples of the present invention and the comparative examples are recorded in Table 1.

[0198] Table 1:

[0199]

[0200] It can be seen from Table 1 that the lithium ion secondary battery prepared in the present invention has good cold start performance, energy density and cycle stability compared with the comparative example.

[0201] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode coating located on at least one side of the positive electrode current collector, wherein the positive electrode coating comprises a first positive electrode coating and a second positive electrode coating stacked along the thickness direction of the positive electrode sheet, wherein the first positive electrode coating is disposed on at least one side of the positive electrode current collector, and the second positive electrode coating is disposed on a surface of the first positive electrode coating away from the positive electrode current collector; The first positive electrode coating includes a first lithium iron phosphate, and the second positive electrode coating includes a second lithium iron phosphate; the average particle size of the first lithium iron phosphate is 500nm-1600nm, and the average particle size of the second lithium iron phosphate is 1.6μm-15μm; The second lithium iron phosphate includes secondary particles, and the first lithium iron phosphate includes a single particle.

2. The positive electrode sheet according to claim 1, wherein: The ratio of the vertical distance from the second lithium iron phosphate to the positive electrode current collector to the thickness of the positive electrode coating is 1:(1.2-12); Preferably, the ratio of the vertical distance from the second lithium iron phosphate to the positive electrode current collector to the thickness of the positive electrode coating is 1:(1.5-8); And / or, the average particle size of the first lithium iron phosphate is 700nm-1500nm, and the average particle size of the second lithium iron phosphate is 2μm-10μm.

3. The positive electrode sheet according to claim 1, wherein: The secondary particles include a plurality of primary particles, and the ratio of the average particle size of the primary particles to the average particle size of the first lithium iron phosphate is 1:(1.25-40); preferably 1:(2.33-10); And / or, the average particle size of the primary particles is 50nm-400nm; preferably 150nm-300nm.

4. The positive electrode sheet according to claim 1, wherein: The first positive electrode coating further includes a first positive electrode conductor, and the second positive electrode coating further includes a second positive electrode conductor; the mass content of the second positive electrode conductor in the second positive electrode coating is less than or equal to the mass content of the first positive electrode conductor in the first positive electrode coating.

5. The positive electrode sheet according to claim 1, wherein: The ratio of the average particle size of the second lithium iron phosphate to the thickness of the positive electrode coating on either side of the positive electrode current collector is 1:(1.6-85); preferably 1:(5-37); And / or, the thickness of the positive electrode coating on any side of the positive electrode current collector is 25 μm-130 μm; preferably 55 μm-80 μm; And / or, the thickness of the first positive electrode coating is 5 μm-90 μm, and the thickness of the second positive electrode coating is 5 μm-90 μm.

6. The positive electrode sheet according to claim 1, wherein: The porosity of the positive electrode sheet is 25%-60%, preferably 30%-50%; And / or, the sphericity of the second lithium iron phosphate is 0.2-1; preferably 0.6-1.

7. The positive electrode sheet according to claim 1, wherein: The first lithium iron phosphate and the second lithium iron phosphate contain element Ti, the mass content of element Ti in the first lithium iron phosphate is C1, the mass content of element Ti in the second lithium iron phosphate is C2, and the ratio of C2 to C1 is 1:(1.5-50); preferably 1:(2.78-16); and / or, C1 is 3000ppm-10000ppm, C2 is 200ppm-2000ppm; Preferably, C1 is 5000ppm-8000ppm, and C2 is 500ppm-1800ppm.

8. A lithium ion secondary battery, characterized in that: The lithium-ion secondary battery comprises the positive electrode sheet according to any one of claims 1 to 7.

9. The lithium ion secondary battery according to claim 8, wherein: The lithium-ion secondary battery further comprises a negative electrode sheet and a separator. The negative electrode sheet comprises a negative electrode active material; and the negative electrode active material comprises hard carbon.

10. The lithium ion secondary battery according to claim 9, wherein The ratio of the average particle size of the negative electrode active material to the thickness of the separator is 1:(0.4-5); preferably 1:(0.8-3.6); And / or, the average particle size of the negative electrode active material is 4 μm-20 μm; preferably 5 μm-15 μm.

Citation Information

Patent Citations

  • Lithium iron phosphate thick electrode and preparation method and application thereof

    CN115394961A

  • Spherical repair method of lithium iron phosphate waste

    CN118198556A

  • Positive plate and battery

    CN118841520A